HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP PERILAKU FOOD HANDLERS TENTANG TRAVELER’S DIARRHEA DI DAERAH WISATA KECAMATAN RENDANG, KARANGASEM - Ni Kadek Rima Pebrianti; Putu Ayu Asri Damayanti; Desak Made Widyanthari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Traveler's diarrhea is a diarrhea commonly suffered by tourists due to consuming contaminated food and drink. The process of preparing, processing and serving food by food handlers must be kept clean to reduce cases of traveler’s diarrhea. This study aims to determine the relationship between knowledge and attitudes towards food handlers behavior regarding traveler’s diarrhea in the tourism area of ??Rendang District, Karangasem. The research method was cross sectional analytic study involving all 55 food handlers as respondents. The sample in this study was selected using a total sampling technique. The results of the study on the knowledge of traveler's diarrhea found that the knowledge was 12.73% sufficient and 87.27% poor knowledge; attitudes about traveler's diarrhea was 56.36% positive and 43.64% negative attitudes; behavior about traveler's diarrhea was 72.73% good behavior and 27.27% bad behavior. Analysis of the relationship found that there was a significant relationship between attitudes and behavior of food handlers about traveler's diarrhea in the tourist area of Rendang District, Karangasem (p value 0.001; r= 0.449). On the other hand, there was no relationship between knowledge and behavior of food handlers about traveler's diarrhea in the tourist area of Rendang District, Karangasem (p value 0.059; r= -0.256). Education and training programs on traveler’s diarrhea in food handlers to increase knowledge, attitudes and behavior about traveler’s diarrhea are necessary to help reduce cases of traveler’s diarrhea.